975 SIMPLY-DETECTED INFLAMMATORY BLOOD MARKERS PREDICT INDEXED LEFT ATRIAL VOLUME AMONG PATIENTS UNDERGOING ATRIAL FIBRILLATION CATHETER ABLATION. (15th December 2022) - Valeri, Yari; Compagnucci, Paolo; Volpato, Giovanni; Falanga, Umbero; Parisi, Quintino; Cipolletta, Laura; Ritq, Enrico; Guerra, Federico; Casella, Michela; Dello Russo, Antonio
Abstract: Background: atrial fibrillation (AF) is the most common sustained arrhythmia encountered in clinical practice. Predisposing factors for priming and maintenance of AF include increased left atrial (LA) size, which correlates with LA disease and is a major risk factor for recurrence after AF catheter ablation (CA). The role of inflammation in the pathogenesis of AF and the associated atrial cardiomyopathy has been ill-defined Objective: we hypothesized that simply-detected inflammatory blood markers could correlate with left atrial volume, and thus with the severity of AF-associated atrial cardiomyopathy. Methods: we conducted a retrospective, observational study enrolling 472 consecutive patients (male gender, n= 357, 76%; mean age, 61±11 years) who underwent paroxysmal (n=318) or persistent (n=154) AF CA at our institution. In each patient, widely available laboratory markers of inflammation (C-reactive protein (PCR), uric acid, and red blood cells distribution width [RDW]) were measured prior to CA and correlated to LA volume, using univariable and stepwise multivariable linear regression. Results: the mean left ventricular ejection fraction (EF) was 57, 4±7, 6%, whereas the mean indexed LA volume was 35, 3±11, 9 ml/m2. The mean RDW measured 13, 5±1, 3, the mean PCR value was 0, 5±1 mg/L, and the mean uric acid value was 5, 2±1, 4 mg/dl. In univariable linear regression analysis, RDW (β 2.65; 95% CI [1.81-3.49]; p=0.0002), PCR (β 1.2; 95% CI [0.02-2.38]; p=0.047), CHA2DS2VASc (β 2, 17; 95% CI [1.42-2.94]; p 0.001), uric acid (β 0.85; 95% CI [0.01-1.69]; p=0.05), EF (β -0.37; 95% CI [-0.51-0.23]; p=0.002) and age (β 0.35; 95% CI [0.25-0.45]; p=0.00004) were significantly related to LA volume. In multivariable linear regression model, EF (β -0.24; 95% CI [-0.39- -0.09]; p 0.002), age (β 02; 95% CI [0.08-0.32]; p 0.0017) and RDW (β 1.5; 95% CI [0.62-2.38]; p 0.00093) retained their independent association with LA volume. Conclusion: RDW, a simple-detected blood marker, proved to be an independent predictor of LA size, suggesting a mechanistic link between inflammation and the severity of atrial cardiomyopathy. These observations may allow a very simple and low-cost identification of AF patients at higher risk of adverse outcomes and recurrences after CA, facilitating treatment plan decisions (e.g., rate vs. rhythm control).